Exercice 1
Factoriser les expressions suivantes :
A = (x + 1)(2x − 1) (x + 1)(3 x - 2)
B = (3x - 7)(2x + 1) − (3x - 7)(5x − 7)
C = (8x + 3)(5x - 7) − 3(8x + 3)(2x − 1)
Exercice 2
Factoriser les expressions suivantes :
D = (2x + 3)² + (x – 2)(2x + 3)
E = (2x – 7) – (5x + 1)(2x – 7)
F = 16y² – 4y
G = (2y – 3)² + (2y – 3)(y – 1) + 2y – 3
Exercice 3
Factoriser les expressions suivantes :
I = (x – 4)² – (2x – 1)²
J = 3(3x - 4)² - 81
K = 2x² - 4(5x + 1)²
Exercice 4
Factoriser les expressions suivantes :
L = 25x² - 9
M = (4 – x)² – 16
N = 64 - 5(x + 1)²
Aucun commentaire:
Enregistrer un commentaire